Membangun Kepemimpinan Masa Depan Berbasis Nilai - Marniyati, Sabar (Responsibilitas, 2010)
Leadership bases on value shall can be made momentum to all leader to preparÃ© it self in order to become successful leader. Opinion sight to leadership bases on value will be able to change opinion sight and behavior of a leader of future. On that account, to build leadership in front hence early on need to be created someone character who is having honestly value, integrity, advantage, humanitarian, and opportunity. Leader of also must have 4 base principle to can form company culture bases for that is needing existence of seriousness from all party involving in forming leadership of future being based on value jointly.